Political freedom and corporate payouts - Guedhami, Omrane; Kwok, Chuck C.Y.; Shao, Liang (Journal of Corporate Finance, 2017)
We study the effect of a country's political freedom status on corporate payouts around the world. In both OLS and two-stage regressions, we find that firms in less free countries pay out more cash, suggesting that low political freedom is associated with a less friendly investment environment. Consistent with this view, we further find that firms reduce payouts when a country's political freedom status improves, while they tend to pay out past excess cash and cut future investment in the face of a deterioration in political freedom. In additional analysis, we also find that firms in less free countries do not pay out cash mainly to ease agency concerns: cash payouts in these countries are more volatile and hence less valuable.